Medical and geographical determinants of oncopathology in the population - M. P. Hrebniak; O. V. Kirsanova; V. V. Taranov; N. H. Mikriukova (Zaporozhye State Medical University, 2021)
The aim: to study the permanent risk factor of oncopathology in order to determine its medical and geographical features and assess their impact on oncopathology of the population of Zaporizhzhia region. Materials and methods. By means of spatial and geographical, as well as analytical and statistical methods, territories were medically and statistically differentiated, with the assessment of the natural environment quality. Epidemiological study of malignant neoplasms was conducted retrospectively for the period of 2004-2015, in accordance with the International Classification of Diseases ICD-10. Determination of environmental impact on oncopathology was performed using the attributive fraction. Results. Geoactive space is characterized by a variety of natural and climatic conditions of lithosphere, hydrosphere and landscapes. The main physical and geographical objects of the Zaporizhzhia region (Ukrainian Crystal Shield, the Dnipro, the Sea of Azov) form six zones, which differ in the diversity of system-forming elements. Specific features of discontinuous disturbances of the lithosphere of the Ukrainian crystal shield are abnormally high electrical conductivity of the earth's crust, intense electromagnetic fields, high concentration of radon in aquifers, and streams of high-energy fluids. Conclusions. The highest geopathogenic impact is manifested in the fault zone of the Ukrainian crystal shield. The highest values of the attributive fraction of malignant neoplasms were registered in this zone among the whole population (26.8 %), among the adult population (25.4 %) and the able-bodied population (32.7 %). The oncopathological potential of natural conditions was least manifested in the valley of the Dnipro breakthrough and the Azov Upland, where the attributive fraction for almost all indicators did not exceed 8.2 %.